Contesting and reinforcing the future of 'meat' through problematization: Analyzing the discourses in regulatory debates around animal cell-cultured meat. Issue 127 (December 2021) - Evans, Brodie; Johnson, Hope
Highlights: Animal cell-cultured meat has been discursively positioned as the solution to global food systems issues. This has impacts on regulatory scope and responses. Current problematizations serve the dominant ideology maintaining the intensive use of animals in food systems. There is a need for animal-centered perspectives in policy and regulatory debates around animal cell-cultured meat. Abstract: This paper draws attention to how 'problems' were constructed at the USDA-FDA Joint Public Meeting on Use of Animal Cell Culture Technology in 2018 and the implications of these discursive constructs for the governance of animals in food systems. The findings demonstrate what problems animal cell-cultured meat has been positioned as the solution to, and what problems emerge from this new technology that regulators are expected to respond to. The problem representation and the solutions posed reproduce understandings that normalize and promote high and increasing levels of animal flesh consumption and related intensive uses of animals. With relevance for various academic disciplines, and policy-making and activist communities, this analysis offers insight from a critical animal studies lens into the role discourse plays in the governance of food systems that in turn shape the lives and bodies of animals in this emerging regulatory space.